Contribution core stability and strength to the performance athlete Slalom Number Water Ski in terms of gender Characteristics - Uzizatun Maslikah; Fahmy Fachrezzy; Haris Nugroho (International Journal of Science, Technology & Management, 2021)
The purpose of this study is to find out the contribution of core stability and strength to the performance athletes slalom number Water Ski in Jakarta in terms of gender characteristics. This research is a survey study using correlational design, while this study was conducted in lake Sunter Jakarta with a sample number of 15 male athletes slalom number water ski. This research instrument uses core stability and strength tests and measurements. For core stability use the ability to fight prisoners' lumbar-pelvic-hip muscles and to strength using tests sit_up and Push ups for 60 seconds. The data analysis in this study uses descriptive analysis and inferential analysis. Descriptive analysis aims to obtain average values,standard deviations, minimum values, and maximum values, while for inferential analysis using simple regression and multiple regression at a significant level ?=0.05 overall data analysis using SPSS version 23. The results of this study show that:(1) there is a contribution of core stability to the performance of male athletes; (2) there is a core stability contribution to the performance of male athletes, and (3) there is a simultaneous contribution of core stability strength to the performance of male athletes slalom number Water Ski in the Jakarta. However, this study only involved a few physical components, for further research to consider the social environment, psychology athletes, and those associated with improving the performance of athletes athlete reviewed from gender.